2005
DOI: 10.1007/bf03022062
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Doppler and thermodilution are not interchangeable for determination of cardiac output

Abstract: Purpose: This study compares thermodilution cardiac output (TD-CO) and esophageal Doppler cardiac output (ED-CO) during periods of hemodynamic stability and after heart stabilization during off-pump coronary artery bypass (OPCAB) surgery. Methods:After Institutional Review Board approval, 58 patients undergoing OPCAB had simultaneous comparison of TD-CO and ED-CO at three time periods. Measurements were recorded, in a blinded manner, after probe insertion (T0), immediately before and after (T1,T2) heart displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Indeed, using TEE and transesophageal echo-Doppler techniques, values similar to those obtained by PRAM are reported [7,8]. Unfortunately, however, intracardiac volumes using TEE and SV determined by the echoDoppler-velocimetry method underestimate by 20-30% SV obtained by magnetic resonance imaging, cineventriculography, and TDCO [11][12][13][14][15][16]. With respect to CI/CO determination by means of ICG in the morbidly obese patient during ppn, Aloni et al [9] reported values essentially equivalent to the TDCO studies of Nguyen et al and Artuso et al Review of the literature, however, shows that ICG systematically underestimates TDCO/ TDCI in the morbidly obese and critically ill patient by 15-20% [17,18].…”
mentioning
confidence: 54%
“…Indeed, using TEE and transesophageal echo-Doppler techniques, values similar to those obtained by PRAM are reported [7,8]. Unfortunately, however, intracardiac volumes using TEE and SV determined by the echoDoppler-velocimetry method underestimate by 20-30% SV obtained by magnetic resonance imaging, cineventriculography, and TDCO [11][12][13][14][15][16]. With respect to CI/CO determination by means of ICG in the morbidly obese patient during ppn, Aloni et al [9] reported values essentially equivalent to the TDCO studies of Nguyen et al and Artuso et al Review of the literature, however, shows that ICG systematically underestimates TDCO/ TDCI in the morbidly obese and critically ill patient by 15-20% [17,18].…”
mentioning
confidence: 54%
“…Previous studies found that hypovolemia and severe hypotension could reduce the blood ow of renal and gastrointestinal to change the distribution of blood ow between upper and lower body [12,13]. Low CO, which was fairly common during off-pump coronary artery bypass graft, leaded to the upper body blood ow probably higher than 30% of CO [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies generally were performed in patients under stable hemodynamic conditions. In contrast, esophageal Doppler had poor agreement with PAC in patients undergoing off-pump coronary artery bypass surgery [19,20]. Based on these inherent limitations of esophageal Doppler devices, their utility appears to be limited to patients in the cardiac surgery population who are hemodynamically stable and in the presence of skilled operators.…”
Section: Flotrac/vigileo Systemmentioning
confidence: 94%